2020
DOI: 10.1590/1807-3107bor-2020.vol34.0052
|View full text |Cite
|
Sign up to set email alerts
|

DEC1: a potential biomarker of malignant transformation in oral leukoplakia

Abstract: Haofeng XIONG (b) Xin HU (a) Yue HU (a) Can WANG (a) Liudi YANG (a) Danni HUANG (a) Kun XIA (b) Tong SU (a)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…In our previous studies, DEC1 had been initially confirmed involving in the development and prognosis of OSCC, 10 and could promote OSCC cells migration induced by hypoxia‐inducible factor‐1α 11 . Moreover, our study in oral leukoplakia (OLK) supported that DEC1 may play important role in the malignant transformation of oral mucosa 12 . However, the mechanism of DEC1 in the progression of OSF and whether DEC1 is involved in the malignant transformation of OSF remain unknown.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…In our previous studies, DEC1 had been initially confirmed involving in the development and prognosis of OSCC, 10 and could promote OSCC cells migration induced by hypoxia‐inducible factor‐1α 11 . Moreover, our study in oral leukoplakia (OLK) supported that DEC1 may play important role in the malignant transformation of oral mucosa 12 . However, the mechanism of DEC1 in the progression of OSF and whether DEC1 is involved in the malignant transformation of OSF remain unknown.…”
Section: Introductionsupporting
confidence: 60%
“…11 Moreover, our study in oral leukoplakia (OLK) supported that DEC1 may play important role in the malignant transformation of oral mucosa. 12 However, the mechanism of DEC1 in the progression of OSF and whether DEC1 is involved in the malignant transformation of OSF remain unknown. Therefore, we speculate that studying DEC1 in OSF may help us understand the mechanism of OSF carcinogenesis.…”
mentioning
confidence: 99%
“…3 C–I) [23 , 24] . Likewise, the expression of survivin, a major antiapoptotic protein [14] , is significantly higher in DEC1 +/+ than DEC1 −/− CRC mice ( Fig. 3 C, F).…”
Section: Discussionmentioning
confidence: 86%
“…Differentiated embryonic chondrocyte expressed gene 1 (DEC1, BHLHE40) belongs to the superfamily of the basic helix-loop-helix (bHLH) transcription factors [13] . This transcription factor has a broad tissue distribution and is involved in diverse cellular events such as differentiation, proliferation and apoptosis [14] . Physiologically, DEC1 is a clock gene and regulates circadian rhythmicity and metabolic functions [14 , 15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation